KONSTRUKSI GERAKAN SOSIAL : EFEKTIVITAS GERAKAN LINGKUNGAN HIDUP GLOBAL - Alfian Hidayat (Jurnal Administrative Reform, 2017)
The Global environmental movement is getting stronger. The models and patterns of movement have constructed new global environmental norm and values. Main agenda of this movement is resistance to global environmental regime which has not been able to solve environmental problems. This paper  found that the environmental movement is successful on conducting environmentalist community and constructing “Go green” such as green discourse in global production and consumption.